2022
DOI: 10.1126/sciadv.abn4188
|View full text |Cite
|
Sign up to set email alerts
|

Engineered ACE2-Fc counters murine lethal SARS-CoV-2 infection through direct neutralization and Fc-effector activities

Abstract: Soluble angiotensin-converting enzyme 2 (ACE2) constitutes an attractive antiviral capable of targeting a wide range of coronaviruses using ACE2 as their receptor. Using structure-guided approaches, we developed a series of bivalent ACE2-Fcs harboring functionally and structurally validated mutations that enhance severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) receptor binding domain recognition by up to ~12-fold and remove angiotensin enzymatic activity. The lead variant M81 potently cross-neutra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 80 publications
2
29
0
Order By: Relevance
“…The engineered decoy sACE2 2 .v2.4‐IgG1 has three substitutions compared with wild‐type ACE2 that enhance affinity for S by over an order of magnitude, measured against S proteins from SARS‐CoV‐2 variants predating omicron (Chan et al , 2020, 2021; Zhang et al , 2022). Fusion to the Fc region of IgG1 increases serum stability and virus clearance (preprint: Chen et al , 2021). We recently found that intravenous (IV) administration of sACE2 2 .v2.4‐IgG1 mitigates lung vascular endothelial injury and increases survival in K18‐hACE2 transgenic mice infected with SARS‐CoV‐2 variants (Zhang et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The engineered decoy sACE2 2 .v2.4‐IgG1 has three substitutions compared with wild‐type ACE2 that enhance affinity for S by over an order of magnitude, measured against S proteins from SARS‐CoV‐2 variants predating omicron (Chan et al , 2020, 2021; Zhang et al , 2022). Fusion to the Fc region of IgG1 increases serum stability and virus clearance (preprint: Chen et al , 2021). We recently found that intravenous (IV) administration of sACE2 2 .v2.4‐IgG1 mitigates lung vascular endothelial injury and increases survival in K18‐hACE2 transgenic mice infected with SARS‐CoV‐2 variants (Zhang et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…There has been disagreement in the literature as to whether sACE2‐catalyzed turnover of vasoconstrictive and pro‐inflammatory peptides will confer therapeutic benefits or whether it is a safety liability. Many groups knocked out the catalytic activity when developing candidate decoy receptors, negating ill‐defined risks of adverse hypotension (preprint: Cohen‐Dvashi et al , 2020; Glasgow et al , 2020; preprint: Iwanaga et al , 2020; Lei et al , 2020; preprint: Chen et al , 2021; Higuchi et al , 2021; Sims et al , 2021; Tanaka et al , 2021). However, we show here that catalytically inactivated sACE2 2 .v2.4(NN)‐IgG1 is not as effective at prolonging the survival of hACE2 transgenic mice infected with a lethal virus dose, suggesting that the catalytic activity of ACE2 present in the decoy confers additional therapeutic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to define suitable animal models, administration routes, and clinical scenarios where the ACE2-IgM-Fc hexamer can bring the most benefits over other ACE2fusions. Considering the importance of Fc-effector functions for the biological activity of ACE2-Fcs, it will be exciting to see how ACE2-IgM hexamers compare to ACE2-IgG-Fc constructs in terms of in vivo efficacy 24 .…”
Section: Resultsmentioning
confidence: 99%
“…The weekly injections of rACE2-Fc effectively lowered plasma Ang II and blood pressure, associated with meliorated albuminuria and reduced kidney and cardiac fibrosis [363] . Recently, in a stringent K18-hACE2 mouse model challenged with various SARS-CoV-2 variants, rACE2-Fc counteracts murine lethal SARS-CoV-2 infection through direct neutralization and Fc-effector activities with a broadly effective therapeutics capability [364] .…”
Section: Targeting Counter-regulatory Ras In Hypertensionmentioning
confidence: 99%